Pengaruh Kualitas Produk, Kualitas Layanan, Citra Merek Terhadap Kepuasan Pelanggan Griya Cokelat di Desa Wisata Nglanggeran, Kecamatan Patuk, Kabupaten Gunungkidul - Tri Nurdiyanto; Ida Bagus Nyoman Udayana; Bernadetta Diansepti Maharani (Universitas Batanghari, 2023)
This study aims to analyze whether product quality, service quality, and brand image can affect customer satisfaction at Griya Coklat Nglanggeran which was conducted in Nglanggeran Tourism Village, Patuk District, Gunungkidul Regency. This research is a quantitative study using a questionnaire distribution technique to all consumers at Griya Coklat Nglanggeran who are the samples in the study. The sampling technique used in this study was a purposive non-probability sampling technique using 120 respondents. Data analysis techniques in this study consisted of data quality tests, classical assumption tests, multiple linear regression analysis tests, and hypothesis testing. Data from filling out the questionnaire from this study were then analyzed using the SPSS 25 application. This study gives the result that product quality and service quality have a positive and significant effect on customer satisfaction. However, brand image gives negative results or does not affect customer satisfaction. The results of this study indicate that product quality, service quality, and brand image simultaneously (simultaneously) have a positive and significant effect on customer satisfaction at Griya Chocolate Nglanggeran.